The effect of game on pre-school period (ages 3-6): A review of study - Ozgur Gul (Türk Spor ve Egzersiz Dergisi)
Game which is very efficient in each period of a child’s development has a great importance. That is, game which is such an effective resource to facilititate his harmony with the outside world, contributes to discover a child’s environment, be aware of his abilities when making new experiences and increase them, express his emotions and opinions when speaking, communicate with his environment, adopt some social roles. In this study, it was focused on the importance of game for children in the period which involves the ages 3-6, is called “Pre-School Period”, in other words, “Game Period”. The relevant literature was studied, based on the study findings about this period; a theoretical basis was presented about the effect of game on this period and evaluated as well. In light of this information, when considering the development levels of pre-school children, game must be given necessary importance for children to be healthier in every aspect. The characteristics to be given to children must be provided to them in amusing ways, that is, games as entertaining items of children. Depending on this, all activities must be done in a game format, not only game activities.